Emergency Obstetrics for the Emergency Medicine Provider - Maxwell Ian Cooper; Dimitrios Papanagnou; Mike Meguerdichian; Komal Bajaj (Association of American Medical Colleges, 2016)
Abstract Introduction Emergency medicine physicians must have the knowledge and skills to stabilize all life-and-limb-threatening conditions. These skills are especially important considering that the 1989 COBRA act clearly defines active labor as a condition unsuitable to transfer. Given this context, we thought it necessary to create a work that could be used to provide emergency physicians with the necessary skills to assist in deliveries both routine and complex. Methods The total time requirement for the workshop is 4 hours. Before the session begins, learners are asked to fill out a survey. Learners complete two 40-minute small-group sessions on the topics of normal vaginal delivery and shoulder dystocia with hands-on training with birthing manikins. After a short break learners complete a 65-minute small-group session for breech delivery with hands-on training. Each small-group session is preceded by a whole-group demonstration of required skills lasting 15 minutes as well a mini lecture on maternal hemorrhage and estimation of blood loss. Results Our workshop has been shown to successfully educate emergency physicians with a range of obstetric experience and improve their knowledge base and hands-on skills. One hundred percent of our learners felt this workshop was appropriate for them and met its stated goals. Discussion While this is not the first workshop to educate on obstetric deliveries and their possible complications, it is the first to be created with the emergency medicine provider as the intended audience and the first to create a curriculum around uncomplicated delivery, shoulder dystocia, breech delivery, and postpartum hemorrhage.